Analisis Strategi Bersaing UMKM Dengan Matriks SWOT dan QSPM - Lyoni Elisabet Marpaung; Cici Lestari; Rianita Puspa Sari (Business Management Journal, 2021)
ABSTRACT Toserba Blitz is one of the MSMEs which is engaged in the sale of daily necessities. Every day, Toserba Blitz to provide consumer needs and determine sales strategies to win the sales competition. The purpose’s research is to make the right decisions in determining the sales strategy to win the competition. The method used strategic management matrix formulation which consists of 3 stages, namely the Input Stage using the Internal Factor Evaluation (IFE) Matrix, the External Factor Evaluation (EFE) Matrix, the External Internal Matrix (IE) and the Boston Consulting Group Matrix, Matching stage using SWOT analysis and the decision stage using QSPM (Quantitative Strategic Planning Matrix) method. The results are the highest Total Attractiveness Scores (TAS), 3.03 and 3.76, which are followed by market and product development strategies with total strength and weakness score of 1.88 and total value of opportunities and threats 2.93, and the integration strategy total score of 1.41 and 3.05. Toserba Blitz needs to apply alternative strategy for market penetration, by increasing store employees to increasing sales, increasing sales of latest products, competitive prices, increasing promotions supported by pricing strategy, increasing the uses of customers based on loyalty, increased advertising, offering promotion extensively or increasing publicity. Keywords: Competitive strategy, MSMEs, SWOT Matrix, Quantitative Strategic Planning Matrix (QSPM).